Are food allergic consumers ready for informative precautionary allergen labelling? - Zurzolo, Giovanni A. (Allergy Asthma Clin Immunol, 2017)
Precautionary allergen labelling (PAL) has resulted in consumer confusion. Previous research has shown that interpretive labels (using graphics, symbols, or colours) are better understood than the traditional forms of labels. In this study, we aimed to understand if consumers would use interpretive labels (symbol, mobile phone application and a toll-free number) with or without medical advice that was advocated by the food industry rather than the normal PAL. This is relevant information for industry and clinicians as it provides an insight into the food allergic perception regarding PAL.